Didáctica del inglés = Classroom Practice - Bascón, Jorge (Formación del Profesorado. Educación Secundaria. Serie: Didáctica de las Lenguas extranjeras/Formación y Desarrollo Profesional del Profesorado, 2011)
El presente libro es el segundo de una serie de tres volúmenes que aborda los aspectos más importantes en la didáctica del Inglés como Lengua extranjera para los estudiantes de educación secundaria. Los ocho capítulos de este libro exploran diferentes aspectos de la práctica en el aula: la implementación del currículo; la elección de los materiales de clase; la enseñanza de la gramática, la pronunciación y el vocabulario; el desarrollo de las habilidades instrumentales (listening, speaking, reading y writing); el uso y el aprovechamiento más adecuado de la alfabetización digital; y la gestión eficaz del aula. Cada capítulo incluye tareas para consolidar la información, así como actividades de evaluación más exhaustivas.This book is Volume II in a three volume series addressing the main issues concerning the teaching of English as a Foreign language to secondary school pupils. The eight chapters in this book address different aspects of classroom practice, including implementing a curriculum; choosing classroom materials; working with vocabulary, grammar and pronunciation; developing instrumental skills (listening, speaking, reading and writing); using and exploiting digital literacy and effective classroom management. Each chapter includes tasks for consolidating the information and more extensive assessment tasks.Temas centrales:Table of contents. Introduction. Transforming the Curriculum into Activities and Work for the Classroom. Choosing and Developing Classroom Material. Digital Literacies and the Language Classroom. Developing Productive and Receptive Skills in the Classroom. Vocabulary Instruction in Secondary Schools. Getting Students Interested in Pronunciation: an Interview with Paul Seligson. EffectiveGrammarTeaching. Classroom Management.